Argentina’s Local Crop Biotechnology Developments: Why Have They Not Reached the Market Yet? - Lewi, Dalia Marcela; Vicién, Carmen (Frontiers in Bioengineering and Biotechnology, 2020)
Plant biotechnology in Argentina started at the end of the 1980s, leading to the development of numerous research groups in public institutions and, a decade later, to some local private initiatives. The numerous scientific and technological capacities existing in the country allowed the early constitution in 1991 of a sound GMO Biosafety regulatory system. The first commercial approvals began in 1996 and to date 52 events have obtained permits to place them on the market, albeit only two were developed locally by public-private partnerships. The transgenic events that have been developed at public institutions pursue different objectives in diverse crops. However, once these events are developed at laboratories, it is difficult to move towards a possible commercial approval. In this work we analyze several reasons that could explain why local developments have not reached approvals for commercialization, stressing those aspects related to the lack of strategic vision in the institutions to focus resources on projects to develop biotechnological products. In that sense, some of the aspects considered are forming a regulatory affairs platform for the public scientific system and the reinforcement of those laboratories that perform tests that are required under the Argentinean regulation.